2014
DOI: 10.1007/s10753-014-9926-x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Corticosteroids Do Not Revert the Activated Phenotype of Eosinophils in Eosinophilic Esophagitis but Decrease Surface Levels of CD18 Resulting in Diminished Adherence to ICAM-1, ICAM-2, and Endothelial Cells

Abstract: Swallowed topical corticosteroids are the standard therapy for eosinophilic esophagitis (EoE) in adults. Eosinophils in the blood of untreated EoE patients have an activated phenotype. Our aim was to determine if corticosteroids restore the phenotype of eosinophils to a healthy phenotype and if certain cell-surface molecules on blood eosinophils correlate with eosinophilic infiltration of the esophagus. Levels of eight surface markers on eosinophils from treated and untreated EoE patients were determined by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The children and adults with EoE had three main findings in common: (i) a higher proportion of their eosinophils expressed CRTH2; (ii) they had lower levels of CD44 on the eosinophil surface; and (iii) their eosinophils had higher levels of mRNA for galectin‐10 than the eosinophils of healthy controls (Table ). As previously reported, the blood eosinophils of adults with EoE had higher levels of CD54 and FOXP3 protein than those from healthy adults—a pattern that was not seen among the children with EoE (Table ). In particular, a discrepancy was noted regarding the eosinophil FOXP3 mRNA levels, whereby the children with EoE had a median fivefold lower level of this mRNA than the healthy children (Figure D), and the adults with EoE had a 3.6‐fold higher FOXP3 mRNA level than the healthy adults (Table ).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The children and adults with EoE had three main findings in common: (i) a higher proportion of their eosinophils expressed CRTH2; (ii) they had lower levels of CD44 on the eosinophil surface; and (iii) their eosinophils had higher levels of mRNA for galectin‐10 than the eosinophils of healthy controls (Table ). As previously reported, the blood eosinophils of adults with EoE had higher levels of CD54 and FOXP3 protein than those from healthy adults—a pattern that was not seen among the children with EoE (Table ). In particular, a discrepancy was noted regarding the eosinophil FOXP3 mRNA levels, whereby the children with EoE had a median fivefold lower level of this mRNA than the healthy children (Figure D), and the adults with EoE had a 3.6‐fold higher FOXP3 mRNA level than the healthy adults (Table ).…”
Section: Resultssupporting
confidence: 76%
“…We have previously reported that the blood eosinophils of adult patients with EoE express a distinctive molecular pattern compared with that of healthy controls and patients with other eosinophil‐associated conditions, that is, allergic rhinoconjunctivitis and ulcerative colitis . Herein, we report that the eosinophils of children with EoE also differ with respect to their molecular pattern when compared with the eosinophils of healthy children.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The peripheral eosinophils are then primed for systemic and local chemokine that ultimately direct eosinophils to the esophagus. Peripheral eosinophils from EoE patients are primed for recruitment with enhanced expression of CRTH2 (receptor for chemoattractant prostaglandin D2)[55], adhesion molecule ICAM-1 [55,56], and CCR3 (receptor for eotaxin-3)[57]. In the esophagus, local cytokines activate eosinophils to release eosinophil granule proteins such as major basic protein-1, eosinophil-derived neurotoxin, eosinophil cationic protein, and eosinophil peroxidase by cytolytic degranulation [58].…”
Section: Eosinophilsmentioning
confidence: 99%
“…Steroid treatment downregulated IL-5 gene expression in the human esophagus [95] and attenuated IL-5-induced esophageal inflammation in mice [40]. After steroid therapy, eosinophils from EoE patients had decreased surface marker CD18 which might impair cell adhesion [56]. Expression of mast cell-associated genes were significantly decreased after steroid treatment in EoE patients [76].…”
Section: Steroid Therapymentioning
confidence: 99%